The bounds of liberty: lessons learnt from treating a man with alcohol use disorder, autism and learning disability. Issue 1 (2nd January 2018) - Drake, Alexander C.L.; Hank, Dietmar; Edwards, Richard; Ensum, Ian; Bateman, Lee
Abstract : Purpose: A man in his 40s with alcohol use disorder, learning disability and autism was referred to the learning disability team due to anxiety and low mood. He had been abstinent from alcohol for ten years prior to a recent relapse. The purpose of this paper is to describe his case. Design/methodology/approach: Treatment was person centred, followed standard practice for clients with alcohol use disorder and targeted harm minimisation. Initially, alcohol consumption reduced; however, at month three, he relapsed. Thereafter, he was repeatedly admitted to inpatient settings, drank excessively and engaged in risky behaviours. Findings: Conventional approaches to treating alcohol dependence may not be entirely appropriate for this client group. The client's alcohol consumption was only curtailed with the use of restrictions to his liberty agreed by him and incorporated into his tenancy agreement. Originality/value: To the best of the authors' knowledge, this is the first paper to discuss issues pertaining to people with co-occurring learning disability, autism and alcohol dependence. The authors discuss the use of restrictions, reasonable adjustments and policy issues relevant to treating this complex client group.